Homonymy in Arabic Vocabular - Muftić, Teufik (Prilozi za orijentalnu filologiju, 2017)
In the introductory part of this study the author deals with the works of some Arabic ancient and modern philologists regarding the researches on the semantics of Arabic language which is important also for the study of the homonymy. Afterwards, he discusses the influence of various endogenous and exogenous forces and factors on the language in general, and especially on the word changes regarding phonetics, morphology and semantics. The influence of foreign words on the creation of new words and new meanings is also mentioned. There is, as well, the influence of various changes of meaning throughout longer or shorter periods of time. Such changes originated in different ways, as for example: extension or restriction of meaning, figurative use of the words because of the amelioration or depreciation of the original (neutral, intellectual) meaning of the word, under the influence of the emotional or volitive component of human spiritual being. In the other, special part, the author discusses the homonyms in Arabic language. At the very beginning he points out the difference between homonymy on one side and polysemy, homophony and homographs on the other side. Afterwards, (according to V.M.Belkin) he explains the differences between so called complete and incomplete homonyms in Arabic vocabulary. Then he gives the list (with the examples) of the three most frequent groups of homonyms: lexical, derivational and grammatical. lt is shown, as well as in the first classification, the origin of the homonyms in all that groups, and also their characteristics on the basis of which they differ from each other. In the third, final part it is shortly exposed the influence of various factors, mainly semantical (for ex. synonymity) either on the creation or on the lost of the homonyms or some of their meanings only. The question is asked concerning the number of the meanings of some homonyms, and how much that number influences on their survival in language and their removal from the use. It is also pointed out the negative side of the existance of the semantically unconnected numerous meanings of some homonyms, because it causes the vagueness and misunderstandings in communication. However, in spite of that, more attention ought to be payed to the phenomenon of homonymy and other characteristics of Arabic language that relates to it, because of their importance in general, and especially in connection with the standardization of Arabic language.